A Brush Seals Program Modeling and Developments - Robert C. Hendricks; Ralph Flower; Harold Howe (International Journal of Rotating Machinery)
Some events of a US Army/NASA Lewis Research Center brush seals program are reviewed, and the development of ceramic brush seals is described. Some preliminary roomtemperature flow data are modeled and compare favorably to the results of Ergun.